2002
DOI: 10.1089/08828240260066260
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a Strong HIV-Specific CD8+T Cell Response in Mice Using a Fowlpox Virus Vector Expressing an HIV-1 Multi-CTL-Epitope Polypeptide

Abstract: Recombinant avipoxvirus vectors are attractive candidates for use in vaccination strategies for infections such as human immunodeficiency virus type 1 (HIV-1), where induction of a CD8+ T cell response is thought to be an important component of protective immunity. Here, we report the expression of a multiepitope polypeptide (TAB9) composed of the central 15 amino acids of the V3 loop from six different isolates of HIV-1 in a fowlpox virus (FWPV) vector, and the use of this vector (FPTAB9LZ) to induce strong H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 83 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…In one recent study, mucosal co-administration of live Lactococcus lactis expressing E7 and IL-12 showed full antitumor protection and prolonged immunity [54]. Moreover, in a number of related studies, the intraperitoneal immunization of different live vaccines has also demonstrated strong protection against HPV-associated or other infections [33,56,57]. As demonstrated in several studies, sc.…”
Section: Discussionmentioning
confidence: 95%
“…In one recent study, mucosal co-administration of live Lactococcus lactis expressing E7 and IL-12 showed full antitumor protection and prolonged immunity [54]. Moreover, in a number of related studies, the intraperitoneal immunization of different live vaccines has also demonstrated strong protection against HPV-associated or other infections [33,56,57]. As demonstrated in several studies, sc.…”
Section: Discussionmentioning
confidence: 95%
“…Several examples already exist for other viruses where replicon-or viral vector-based vaccines expressing transgenic single epitopes or polyepitopes were capable of inducing a CTL response. In many cases, protective immunity upon challenge has even been successfully established [46][47][48][49]. The CSF-VRP, like the virus they are derived from, have a tropism for dendritic cells (DC) and both conventional DCs (cDC) and plasmacytoid DCs (pDC) are early targets for the virus [29].…”
Section: Discussionmentioning
confidence: 99%